Refractometric Sensitivity Enhancement of Weakly Tilted Fiber Bragg Grating Integrated with Black Phosphorus - Zhao Zhang; Kun Liu; Junfeng Jiang; Tianhua Xu; Shuang Wang; Jinying Ma; Pengxiang Chang; Jiahang Zhang; Tiegen Liu (Nanomaterials, 2020)
The sensitivity enhancement of the weakly tilted fiber Bragg grating (WTFBG) integrated with black phosphorus (BP) was investigated via numerical simulations and experimental demonstrations. BP nanosheets were deposited twice on the cylindrical WTFBG surface using the in situ layer-by-layer (i-LbL) deposition technique. The resonance intensity of the deepest cladding mode located around 1552 nm of WTFBG had a 9.2 dB decrease after the BP deposition process. This allows for the application of the intensity-modulated refractive index (RI) sensor. The sensing platform was implemented on the use of the BP integrated with WTFBG (BP-WTFBG). The refractometric sensing was achieved with the sensitivity enhancement of the resonance intensity modulation of the deepest cladding mode for the BP-WTFBG. The sensitivities were 137.6 dB/RIU and 75.6 dB/RIU in the RI region of 1.33–1.35 and 1.35–1.38, respectively. This platform shows great potential applications for biochemical sensing because of its highly sensitive RI sensing ability around the biochemical sensing window.